2009
DOI: 10.1002/lt.21883
|View full text |Cite
|
Sign up to set email alerts
|

Differential transcriptome patterns for acute cellular rejection in recipients with recurrent hepatitis C after liver transplantation

Abstract: Histopathological evaluation of the liver via biopsy remains the standard procedure for the diagnosis of both acute cellular rejection (ACR) and recurrent hepatitis C (RHC) after liver transplantation. Nevertheless, it is often difficult to diagnose ACR in hepatitis C virus–positive recipients because of changes in common and overlapping with RHC. The aim of this study was to identify potential target genes for ACR in recipients with RHC. We analyzed 22 liver biopsy samples obtained from 21 hepatitis C virus–p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 29 publications
0
21
1
Order By: Relevance
“…In contrast, one of the major findings of the present study concerns the relationship between ISG expression in the graft and subsequent development of acute rejection. We and others [21][22][23]; being based on protocol biopsies, however, the present data suggest that ISG activation precedes and may be causally related to acute rejection. This hypothesis is supported by the observation that, by virtue of its immune-stimulating properties, interferon alpha treatment of recurrent hepatitis C may facilitate rejection [24].…”
Section: Discussioncontrasting
confidence: 63%
“…In contrast, one of the major findings of the present study concerns the relationship between ISG expression in the graft and subsequent development of acute rejection. We and others [21][22][23]; being based on protocol biopsies, however, the present data suggest that ISG activation precedes and may be causally related to acute rejection. This hypothesis is supported by the observation that, by virtue of its immune-stimulating properties, interferon alpha treatment of recurrent hepatitis C may facilitate rejection [24].…”
Section: Discussioncontrasting
confidence: 63%
“…Recent advances in genetic information using high throughput microarray analysis has revealed that there are quite different transcriptome patterns according to the rejection status after solid organ transplantation (5)(6)(7)(8). We already revealed that small bowel allografts undergoing ACR show distinct mRNA expression profiles involving immune, inflammatory and apoptosis genes reflect the histopathological changes in bowel biopsies and provided novel insights into these pathways operative in alloreactive inflammation (9).…”
Section: Introductionmentioning
confidence: 92%
“…Thus, it would be ideal to have an accurate, reproducible, and noninvasive method to diagnose the cause of allograft dysfunction after liver transplantation. We approached this issue previously using transcriptome analysis of liver biopsy and peripheral blood using both an animal model [19] and human samples [20,21] and identified candidate markers associated with ACR. These studies should be continued for further validation of these candidate genes in liver and peripheral blood.…”
Section: Discussionmentioning
confidence: 99%